First Description of Reduced Pyruvate Dehydrogenase Enzyme Activity Following Subarachnoid Hemorrhage (SAH) - Lilla, Nadine; Füllgraf, Hannah; Stetter, Christian; Köhler, Stefan; Ernestus, Ralf-Ingo; Westermaier, Thomas (Frontiers in Neuroscience, 2017)
Object: Several previous studies reported metabolic derangements and an accumulation of metabolic products in the early phase of experimental subarachnoid hemorrhage (SAH), which may contribute to secondary brain damage. This may be a result of deranged oxygen utilization due to enzymatic dysfunction in aerobic glucose metabolism. This study was performed to investigate, if pyruvate dehydrogenase enzyme (PDH) is affected in its activity giving further hints for a derangement of oxidative metabolism. Methods: Eighteen male Sprague-Dawley rats were randomly assigned to one of two experimental groups (n = 9): (1) SAH induced by the endovascular filament model and (2) sham-operated controls. Mean arterial blood pressure (MABP), intracranial pressure (ICP) and local cerebral blood flow (LCBF; laser-Doppler flowmetry) were continuously monitored from 30 minutes before until 3 hours after SAH. Thereafter, the animals were sacrificed and PDH activity was measured by ELISA. Results: PDH activity was significantly reduced in animals subjected to SAH compared to controls. Conclusion: The results of this study demonstrate for the first time a reduction of PDH activity following SAH, independent of supply of substrates and may be an independent factor contributing to a derangement of oxidative metabolism, failure of oxygen utilization and secondary brain damage.